Keterkaitan Antara Minat Belajar Siswa Dengan Metode Pembelajaran Pendidikan Agama Islam - Asqhalani Winata; Dettismi D; Fenny Ayumonia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Â Islamic Religious Education is one of the subjects that every student must take at school, each student has different interests in the subject of Islamic Religious Education. This research aims to determine students' interest in learning in Islamic Religious Education subjects at SMAN 2 Tilatang Kamang. This research uses a qualitative approach - descriptive type with field study methods. The results of this research show that students' interest in learning PAI consists of aspects: First, students show full attention to PAI subjects. Second, use students' free study time normally to study PAI. Third, student participation in spiritual learning and extracurricular activities has a positive and enthusiastic response. Thus, the student's interest in learning is good in PAI subjects.